Investigation of Changing Volt-Ampere Characteristics of AlGaInP Heterostructures with Multiple Quantum Wells under Ionizing Radiation; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Gradoboev A. V. Aleksandr Vasilyevich (2016, 2016)
Title screen